Trends of Incidence and Survival Rates of Mucosa-associated Lymphoid Tissue Lymphoma in the Korean Population: Analysis of the Korea Central Cancer Registry Database - Jeong, Seok-Hoo (J Korean Med Sci, 2020)
BACKGROUND: Extranodal marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue (MALT-lymphoma) is an extranodal lymphoma that occurs at various sites in the body. There is a limited understanding of the incidence and survival rates of MALT-lymphoma. To investigate the nation-wide incidence and survival rates of MALT-lymphoma in Korea during 1999–2017, the data on MALT-lymphoma were retrieved from the Korea Central Cancer Registry. METHODS: During the time period of 1999–2017, 11,128 patients were diagnosed with MALT-lymphoma. The age and sex of the patients and the Surveillance, Epidemiology, and End Results (SEER) summary stage of the tumor were analyzed, and the relative survival rates (RSRs) were calculated. RESULTS: The age-standardized incidence rates of MALT-lymphoma in 2017 among males and females were 1.53 and 1.61 per 100,000 individuals, respectively, whereas those in 1999 among males and females were 0.21 and 0.20, respectively in Korea. The RSRs were more than 97% at 10 years post-diagnosis between 1993 and 2017. The 5-year RSRs were 87.4%, 94.8%, 97.8%, and 98.6% during 1996–2000, 2001–2005, 2006–2010, and 2013–2017, respectively. Based on SEER summary staging, the 5-year RSRs during 2013–2017 were 100.3%, 90.8%, 91.3%, and 97.9% for patients with localized, regional, distant, and unknown stages of MALT-lymphoma, respectively. CONCLUSION: Although the incidence of MALT-lymphoma is low in Korea, it has been increasing in recent years. The prognosis of MALT-lymphoma is good even at advanced stages. These findings provide useful insights to clinicians about MALT-lymphoma and inform patients about the survival rate.